Teratogenic and Embryocidal Effects of Zidovudine (AZT) in Sprague-Dawley Rats - James T. Christmas; Bertis B. Little; Kraig A. Knoll; Roger E. Bawdon; Larry C. Gilstrap III (Hindawi Limited, 1995)
Objective: The purpose of the present investigation was to analyze the effets of zidovudine on the postimplantation embryo and fetus.